Chapter 8 Non- South African SADC Navies and Maritime Security in the Post- Cold War Era Angola and Mozambique - Ndawana, Enock (Taylor & Francis, 2022)
Africa, Cape of Good Hope, maritime security, naval history, piracy, Suez Canal